Prognostic significance of tumor-associated macrophages: past, present and future. (April 2020) - Cortese, Nina; Carriero, Roberta; Laghi, Luigi; Mantovani, Alberto; Marchesi, Federica
Highlights: Macrophages (Mφ) densely infiltrate cancer tissues and correlate with clinical outcome. Mφ prognostic value varies according to tumor type and therapy. Assessment of macrophages ranges from morphological classification to omics approaches. Single-cell based technologies can dissect Mφ heterogeneity in tumors to identify novel prognostic markers. Abstract: Tumor tissues are populated by a multitude of macrophages, highly different in functional activity, localization and morphology. A clear contribution to disease progression has been shown in multiple cancer types, holding promise for the development of innovative macrophage-based prognostic tools. Current studies aimed at assessing the prognostic role of macrophages have documented the relevance of the macrophage population as a whole. However, dissecting the diversity of mononuclear phagocytes in tumor tissues has provided important information about the coexistence of distinct populations of macrophages with different prognostic significance. Here we summarize evidence of macrophage prognostic function in human cancer and focus on classical and modern strategies aimed at measuring macrophage features and deciphering their diversity. The wealth of new data generated will reshape our knowledge of macrophage complexity and hopefully foster the forthcoming development of these new metrics into prognostic tools as well as new therapeutic strategies.